Radical Pedagogies and Metamodelings of Knowledge in the Making - Manning, Erin (Critical Studies in Teaching and Learning, 2023)
Across three scenes, this proposition explores the place of knowledge in experience, asking how else we might think of radical pedagogy. Inspired by the work of Loris Malaguzzi and oriented by the wander lines of autistics who refuse to adapt to neurotypical modes of knowing, the hope is to follow transversal diagrams rather than premade maps of what education can be. Decolonial practices for rethinking education are central to this neurodiverse reorientation of the map.